Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 2 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Lophostoma evotis (Davis & Carter, 1978)", "Country is Mexico", "HasGeospatialIssue is false", "HasCoordinate is true", "BasisOfRecord is Specimen" ] } The dataset includes 2 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006273-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences